SURGICAL MANAGEMENT OF SERTOLI CELL TUMOR IN A SHIH TZU DOG - T. Sarath; P. Jayashree; P. Sankar; S. Manokaran; R. Rajkumar; A. Thangamani; A. Reshma (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 3-year-old cryptorchid Shih Tzu dog presented with the history of swelling near the right side of parapenile region along with development of mammary glands. Palpation of scrotal sac and testis showed that right testis was swollen and undescended, and left side testis was atrophied. Ultrasonographic examination of right testis appeared slightly echogenic and left testis appeared with no details. Orchiectomy was carried out and both the testicles were removed. After surgery histopathological examination confirmed the presence of Sertoli cell tumor. In the present case Sertoli cell tumor is recorded in three-year-old cryptorchid Shih tzu dog and successfully managed with radical surgery.